Extraction of Gaharu oil from Karas (Aquilaria Malacensis) - Mohammad, Noorshashillawati Azura; Kasim, Jamaludin; Daud, Shaari (2011)
Gaharu (agarwood, aloeswood, eaglewood, jinkoh, chen-xiang and aquilaria) have previously been known as highly valuable wood and important source for medical and perfumes due its strong and unique scent. In Malaysia, gaharu may be classified into three species: Aquilaria hirta, A. malaccensis and A. rostrata and they often graded into three grades: Grade A, Band C, according to the physical properties, chemical properties, gaharu formation and unique scent. The lower grades such as Grade C are often distilled to obtain gaharu oils. Gaharu oil was extract from karas by using two different techniques; water distillation and Soxhlet extraction. Identification of the chemical components was analyzed by FTIR, 1H-NMR, GC and GC-MS. Examination of the oils showed some variations and differences in terms of GC profiles, concentration and chemical components. The main component of the oil was 4-phenyl-2-butanone with 22.96%. 1,2benzenedicarboxylic acid, was the second major compounds with 17.04%. Besides of these two chemical components, this oil also contains other compound such as 6ethyl-5-methyl-3-pyridinecarbonitrile (8.79%), hexadecanoic acid (7.61 %) and tritetracontane (6.04%).